Privileges and Immunities of the International Organizations Staff - A. G. Miachina (Евразийская интеграция: экономика, право, политика, 2021)
The article discloses the basic privileges and immunities of the international organizations staff, as established by the provisions of international law. The author considers dispute settlement practices involving international organizations staff to determine compliance with international norm-setting which regulates the law institution in question, including cooperation with the national norm-setting.